Response to combination of mycophenolate mofetil, cyclosporin A and corticosteroid treatment in lupus nephritis patients with persistent proteinuria - Nuntana Kasitanon (2018)
© 2017 Asia Pacific League of Associations for Rheumatology and John Wiley & Sons Australia, Ltd Objective: To study the response of lupus nephritis (LN) patients with persistent proteinuria (≥ 1 g/day after ≥ 6 months corticosteroid and single immunosuppressant treatment, or ≥ 3 g/day after ≥ 3 months of corticosteroid and single immunosuppressant treatment) to corticosteroid combined with two immunosuppressants, and to evaluate associated factors of response within 1 year. Method: A retrospective study of proteinuria and renal function observed in LN patients with persistent proteinuria after adding a second immunosuppressant at 3, 6, 9 and 12 months. Result: Twenty-one LN patients (100.0% female) with persistent proteinuria were treated with corticosteroid and two immunosuppressants (mycophenolate mofetil [MMF] plus cyclosporine A [CSA]). Their mean age and duration from first immunosuppressant to initiating a combination therapy were 33.2 ± 10.2 years and 17.5 ± 15.7 months, respectively. Twelve (57.1%) patients had proteinuria levels ≥ 3 g/day. The renal pathology from 18 patients were Classes III or IV in 11 (61.1%). Fifteen patients (71.4%) responded to treatment (complete remission [CR], proteinuria ≤ 0.5 g/day, in seven patients and partial remission [PR], proteinuria reduced > 50%, in eight patients). Changing from a single immunosuppressant to combined immunosuppressants was associated with CR within 1 year (hazards ratio = 0.88; 95% CI = 0.78–0.99). Adverse events consisted of one patient with severe infection, two herpes zoster and one with transient increased serum creatinine level. Conclusion: Approximately 70% of LN patients with persistent proteinuria responded to MMF plus CSA. However, infection should be a concern with these patients.